I Will Hurt You for This, When and How Subordinates Take Revenge From Abusive Supervisors: A Perspective of Displaced Revenge - Hongbo, Li; Waqas, Muhammad; Tariq, Hussain; Nana Abena, Atuahene Antwiwaa; Akwasi, Opoku Charles; Ashraf, Sheikh Farhan (Frontiers in Psychology, 2020)
Abusive supervision; defined as subordinates’ perception of the extent to which supervisors engage in the sustained display of hostile verbal and nonverbal behaviors, excluding physical contact, is associated with various negative outcomes. This has made it easy for researchers to overlook the possibility that some supervisors regret their bad behavior and express remorse for their actions. Hence, we know little about how subordinates react to the perception that their supervisor is remorseful and how this perception affects the outcomes of supervisors’ undesired behavior. Specifically, drawing on the social exchange theory (SET) and displace revenge literature, this study explains how abusive supervision leads to victims’ service sabotage behavior. Besides, this study also investigates how perceived supervisors’ remorse (PSR) mitigates the adverse effects of abusive supervision. Based on time-lagged, dyadic data (63 supervisors, 212 subordinates) from Chinese individuals, this study found support for all the proposed relationships i.e. abusive supervision leads to service sabotage through the mediating effect of revenge desire. The findings also conclude that PSR lessens the detrimental effects of abusive supervision on victims’ behavior with their customers. Finally, this research contributes to service sabotage literature by highlighting the possibility where abusive supervisors cause service sabotage behavior among victims. This study also shows the importance of PSR's role in decreasing service sabotage behavior exhibited by victims of abusive supervisors in the service sector.